Effectiveness of Using Technology Supportive Materials for Developing Listening Skills among School Children - Sultana, Yeasmin (JOURNAL OF INDIAN EDUCATION, 2016)
Listening occupies a central place in everyday communication as most of our knowledge of the world is derived from listening input. Despite the centrality of listening, it has received an unfair treatment in second language classrooms. This paper discusses why it is imperative to develop listening skills among learners. Besides, it aims to study the effectiveness of using technology supportive materials for developing listening skills in English among school students. Two groups — pre-test and post-test design — was followed in the study. The experiment was conducted for 30 days. Students of two sections of Class VIII constituted the sampling group. An analysis of the data was done using both descriptive and inferential statistics. It is found that the use of technology supportive materials is more effective than the traditional method for developing listening skills in English among school students.